Impact Analysis of Wall-Caisson Composite Structure Construction Adjacent to Rail Transit Bridge - CHEN Wei; NI Lei; ZHOU Yin; DENG Chenglong; DI Honggui; CAO Zhanlin; YAO Qiyu (Chengshi guidao jiaotong yanjiu)
[Objective] The construction deformation control adjacent to operational railways is of utmost importance in current rail transit planning and construction. Therefore, it is necessary to study the effect of the diaphragm wall-caisson composite structure （hereinafter referred to as WCCS）parameters on the structural stress deformation characteristics, which are caused by the caisson interior excavation and the change patterns of the surrounding soil displacement. [Method] In the case study of a composite structure construction project adjacent to Shanghai-Suzhou-Nantong Railway Bridge in Nantong City, the finite-element software is used to analyze the internal forces, deformations, and the surrounding ground settlement patterns of the WCCS. [Result & Conclusion] Firstly, the caisson under the protection of a circular diaphragm wall exhibits relatively small horizontal deformation. Increasing the thickness of both the caisson and diaphragm wall will reduce the maximum deformation and stress in the WCCS itself. However, within the 3~5 m width range of sandwiched soil, the widening of sandwiched soil leads to increased stress and deformation in the diaphragm wall, with a sudden spike particularly observed at the 5 m width of sandwiched soil. Secondly, the uplift value of the bottom-sealed concrete and sandwiched soil is less affected by the thickness of the WCCS. However, within the 3~5 m width range of sandwiched soil, the soil uplift value first increases and then decreases, with the turning point occurring at the 4.5 m width of sandwiched soil. Thirdly, increasing the thickness of the caisson and diaphragm wall reduces the boundary of surrounding ground settlement, with particularly significant weakening effect of the caisson thickness. The width of sandwiched soil has a significant impact on ground settlement, which begins to increase markedly when the width exceeds 3.5 m. Lastly, a well-designed WCCS can improve the stability of the caisson and reduce the deformation impact of caisson construction on the surrounding environment.